Histological studies on the marsupium of two terrestrial isopods (Crustacea, Isopoda, Oniscidea) - Diána Csonka; Katalin Halasy; Elisabeth Hornung (ZooKeys, 2015)
The marsupium, a brood pouch in peracarid crustaceans (Crustacea, Malacostraca) has evolved in terrestrial environment for providing nutrition and optimal conditions for embryogenesis. In the present study we give details on the histology and ultrastructure of its constituting elements such as oostegites and cotyledons. Marsupia of two different eco-morphological types of woodlice, namely the non-conglobating species Trachelipus rathkii Brandt, 1833 and the conglobating species Cylisticus convexus De Geer, 1778 were investigated. Light microscopic (LM) studies showed some differences in the main structure of the two species’ brood pouch: in T. rathkii, a ‘clinger’ type woodlice, the oostegites bend outwards during brood incubation as growing offspring require more space, while in C. convexus, a ‘roller’ type isopod, the sternites arch into the body cavity to ensure space for developing offspring and still allowing conglobation of the gravid females. The quantitative analysis of the oostegites’ cuticle proved that the outer part is about 2.5 - 3 times thicker compared to the inner part in both species. Electron microscopic (TEM) examinations show only small histological differences in the oostegites and cotyledon structure of the two species. Cellular elements and moderately electron dense fleecy precipitate are found in the hemolymph space between the two cuticles of oostegites. The cells contain PAS positive polysaccharide areas. TEM studies revealed some differences in the cotyledon ultrastructure of the two species. Cotyledons of T. rathkii consist of cells with cristate mitochondria and granular endoplasmic reticulum with cisterns. Cotyledons of C. convexus consist of cells with densely cristate mitochondria and ribosomes attached to vesicular membrane structures. In both species cells with electron dense bodies were observed. We conclude that - besides the differences in marsupial shapes - the fine structure of the oostegites and cotyledons is hardly affected by the eco-morphological type, specifically the conglobating or non-conglobating character of the studied species.